Students’ Self-Efficacy and Students’ Speaking Skill: A Correlational Analysis - Rafiqa; Fitriani (Universitas Sulawesi Barat, 2023)
The current research aimed to know the level of the students’ self-efficacy and the correlation between students’ self-efficacy and students’ speaking skills in English. The subject of this research was the students of the Speaking for Academic Purposes class at the fourth semester of the English Education Department at the University of Sulawesi Barat. The total sampling technique was used in this research, and it contained the total active students in the fourth semester of the English education study program was 74 students. The quantitative method was applied in this research, and the design was a correlational study. Furthermore, the instruments attempted were a self-efficacy questionnaire and students’ speaking scores from the Speaking for academic purpose lecturer at the English Education Department at the University of Sulawesi Barat. The first result of this study showed that most of the students had a high level of self-efficacy, and the second result showed that the sig value is 0.81 > 0.05. It can be concluded that rejecting ha and accepting ho means there was no significant correlation between self-efficacy and student's speaking skills.